THU0627 Treatment of rheumatoid arthritis: adherence to guidelines in private practice. (15th June 2017) - Fernandes, LB; Palacios, FA; Lerner, PG; Macedo, CG; Omura, F; Azeka, EAK; Laurindo, IMM; Toth, P; Ferreira, RC; Aurichio, RAO; Bazilio, AP; Brudniewski, J; et al.
Abstract : Background: Guidelines and therapeutic strategies in the treatment of rheumatoid arthritis (RA) have been developed and adopted by most Societies of Rheumatology. However, the extent to which they have been supported by rheumatologists in their individual clinical practice is unclear. Objectives: Our aim was to analyze, at private offices, adherence to guidelines and characteristics of RA patients in regular follow-up. Methods: This was a cross-sectional study developed by a group of rheumatologists (n=13) working exclusively in private offices and hospitals in São Paulo, Brazil. It consisted of a web-based questionnaire addressing patient's demographics, social characteristics and treatment. Patients having the diagnosis of RA should be included sequentially. As Brazil's private health has no reference flowchart, patients can consult any physician from their insurance health program, or any physician at all if bearing the costs. Insurance programs can be either personal or tied to employers, in which case job changes imply in insurance and health professional changes. Results: Data from 235 RA patients were collected, 84% were female, mean age (SD) 57.3 (13.3) yrs., disease duration 9.5 (1–54) yrs., 73% RF positive (74% of the 61 RF negative patients had an anti-CCP test and 8 were positive), The mean duration of symptoms until diagnosis was 1.7yrs (0–23), number of physicians until diagnosis 2.4 (1 – 12), including GP (102 patients), orthopedists (110 patients) and rheumatologists (129 patients). Even after diagnosis, patients switched professionals at a mean number of 2 physicians (1–6), justified by shift of health insurance (66 patients), lack of resolution (33 patients), dislike of the physician (26 patients) and cost (11 patients). Regarding treatment, 51% of patients were on biologic agents: 23% adalimumab, 15% abatacept and rituximab, 14% etanercept, 12% tocilizumab, 7.6% golimumab, 5% certolizumab and infliximab and 4% tofacitinib. Interestingly, most patients (75%) using abatacept, tofacitinib and tocilizumab were not on methotrexate (MTX), while from the 65 patients on an anti-TNF agent, 75% were also using MTX or leflunomide (LFN). Regarding traditional DMARDs, 91% of patients were on (n=94) or had used MTX (n=120); 43% were on (n=37) or had used (n=64) LFN. Concerning treatment and disease activity, 91% of patients were considered adherent to the treatment with a mean number of 4 annual visits, 82% were also deemed to be in regular monitoring. According to rheumatologist's assessment, 63% of patients had RA "under control". In fact, 72% of patients were on low disease activity (22%) or on remission (50%), according to the DAS28. However, when patients in disease activity were analyzed, few of them (0.28 CI 0.18–0.40) were on biologic or target DMARDS, pointing to a possible therapeutic transitional moment. Only 3 of these could be labeled "refractory", having previously used 3 biologic agents. Conclusions: Treat-to-target strategy seems to have been adopted by most rheumatologists in their individual practice, although there is room for improvement and optimization of therapy. While treatment guidelines are roughly followed, the delay in diagnosis and changes of healthcare are particularly worrisome and need to be addressed. Disclosure of Interest: None declared